2014
DOI: 10.1103/physrevstab.17.043402
|View full text |Cite
|
Sign up to set email alerts
|

Emittance, surface structure, and electron emission

Abstract: The emittance of high brightness electron sources, particularly field emitters and photocathodes but also thermionic sources, is increased by surface roughness on the emitter. Such structure causes local field enhancement and complicates both the prediction of emittance and the underlying emission models on which such predictions depend. In the present work, a method to find the emission trajectories near regions of high field enhancement is given and applied to emittance predictions for field, photo, and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 71 publications
2
30
0
Order By: Relevance
“…Yet, as Miller, et al, clearly point out, 9 that conjecture is largely unproven except for special cases (e.g., the 2D rectilinear geometries considered by Miller, et al, using conformal mapping techniques), even as it is an essential component in explaining causes of field emission or dark current, 10 has bearing on the putatively low emission fields suggested to be evinced for otherwise planar emitters (but which, as Forbes, et al, 11 argue, is more complex), or suggested by similar studies. 12 Yet some assessment of the conjecture's applicability, particularly to the conical and / or wire-like emitters of contemporary design, is needed to justify its usage in beam optics codes [13][14][15] in the modeling of those field emitters. Such modeling is essential in the design of high power microwave devices, 16,17 amplifiers, 18 and particle accelerators.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, as Miller, et al, clearly point out, 9 that conjecture is largely unproven except for special cases (e.g., the 2D rectilinear geometries considered by Miller, et al, using conformal mapping techniques), even as it is an essential component in explaining causes of field emission or dark current, 10 has bearing on the putatively low emission fields suggested to be evinced for otherwise planar emitters (but which, as Forbes, et al, 11 argue, is more complex), or suggested by similar studies. 12 Yet some assessment of the conjecture's applicability, particularly to the conical and / or wire-like emitters of contemporary design, is needed to justify its usage in beam optics codes [13][14][15] in the modeling of those field emitters. Such modeling is essential in the design of high power microwave devices, 16,17 amplifiers, 18 and particle accelerators.…”
mentioning
confidence: 99%
“…Such a model is sought to account for the microscale structure of carbon fiber field emitters, as evidenced in Figure 1, so as to enable their simulation in particle-in-cell codes. [13][14][15] The conjecture therefore has a very pragmatic side. In contrast to past treatments of the PCM, the present treatment is rendered analytically, thereby giving insight into how Schottky's conjecture unfolds.…”
mentioning
confidence: 99%
“…The next step is to develop a modified tip current model accounting for the effects of prolate spheroidal geometries on total current per tip models in a manner analogous to previous efforts using the planar image charge approximation. 10 …”
Section: Discussionmentioning
confidence: 99%
“…A simple correction to accommodate curvature effects into the estimate of total current is to incorporate the image charge associated with a hemispherical shape (a staple boundary value problem in electrodynamics textbooks 19,20 and elsewhere 5,21 ) characterized by a tip radius a, by redefining the work function by U a ¼ U þ ðQ=2aÞ in the Fowler-Nordheim equation 5,22 (although important, the modifications to the transmission probability accounting for trajectory curvature effects which increase the tunneling barrier an electron encounters are not part of the present analysis, although they can be included 10,23,24 2 Þ as a function of 1/F in the Fowler-Nordheim representation of data] but also the power that F is raised to in the coefficient (2 -) and the interceptÃ.…”
Section: Spherical Image Charge Approximationmentioning
confidence: 99%
“…Such surface and/or geometric variations result in the detailed beam distribution immediately taking on a fully 3D nature, for example, in a 3D simulation, and the code calculates and predicts this effect. Finally, a remaining multidimensional effect, that of transverse momentum components during emission, 25,26 becomes important when emittance is treated, and is considered separately.…”
Section: C102-3 Jensen Et Almentioning
confidence: 99%